Quantitative urinary tract infection diagnosis of leukocyte esterase with a microfluidic paper-based device. Issue 27 (16th June 2021) - Tseng, Wei-Ting; Tseng, Hsin-Yi; Chou, Yin-Yu; Wang, Yin-Chen; Tseng, Tz-Ning; Ho, Li-Ing; Pan, Sheng-Wei; Ho, Mei-Lin
Abstract : Electrochemical diagnosis of leukocyte esterase for urinary tract infection by using microfluidic paper-based device. Abstract : Leukocyte esterase (LE) is a useful marker that can be used in establishing a diagnosis of urinary tract infections (UTIs). The development of a UTI diagnostic method with quantitative determinations of biomarkers across all age groups is becoming more important. In this report, microfluidic resistance sensors based on silver ink (Ag ink) and silver ink mixed with ZnO nanoparticles (Ag-ZnO ink) were synthesized and coated on cellulose paper, namely LE-Ag-μPADs and LE-Ag-ZnO-μPADs, respectively, for the sensitive detection of LE. The microfluidic design increases the precision of data and further allows for quantitative determination and early detection of LE in human urine. The quantification of LE relies on the change in the resistance readout coating with Ag ink as well as Ag-ZnO ink in the detection zone. A mixture of 3-( N -tosyl-l -alaninyloxy)-5-phenylpyrrole (PE) and 1-diazo-2-naphthol-4-sulfonic acid (DAS) was deposited in the sample zone to selectively recognize LE, and the resulting nonconductive products, i.e., azo compounds, further reacted with the Ag ink and Ag-ZnO ink to increase resistance. The quantitative detectable LE concentrations between 2 to 32 (×5.2 U mL −1 ), i.e. ≈12 to 108 μg L −1, cover the commercial dipstick range of trace, +1 and +2. The minimum detectable concentration of LE in urine was 1 (×5.2 U mL −1 ). The lower concentrations of LE detectable by LE-Ag-μPADs (1–8 × 5.2 U mL −1 ) are below the value achieved with the ELISA LE kit. Urine samples from inpatients with indwelling urinary catheters were used, and the LE levels measured by the present device were highly correlated with those determined by a commercial urine analyser.